Output-based payment to boost staff productivity in public health centres: contracting in Kabutare district, Rwanda - Bruno Meessen; Jean-Pierre I Kashala; Laurent Musango (The World Health Organization, 2007)
OBJECTIVE: In many low-income countries, public health systems do not meet the needs and demands of the population. We aimed to assess the extent to which output-based payment could boost staff productivity at health care facilities. METHODS: We assessed the performance of 15 health care centres in Kabutare, Rwanda, comparing productivity in 2001, when fixed annual bonuses were paid to staff, with that in 2003, when an output-based payment incentive scheme was implemented. FINDINGS: Changes to the structure of contracts were associated with improvements in health centre performance: specifically, output-based performance contracts induced sharp increases in the productivity of health staff. CONCLUSION: Institutional configurations of health care organizations deserve more attention. Those currently in place in the public sector may not the most suitable to meet current challenges in health care. More experiments are needed to confirm these early results from Rwanda and elsewhere, since risks associated with output-based incentive schemes should not be ignored.